Characterization of Mangoes In Cirebon Using The Single Nucleotide Polymorphism Method (Snp) - Chika Septianingsih; Umi Trisnaningsih; Dony Nauphar (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2026)
Mango (Mangifera indica L.) is a leading horticultural commodity in Cirebon Regency, boasting a diverse array of local varieties with distinct fruit characteristics. Varietal identification has traditionally been based on morphological characteristics, but this method is often inaccurate due to environmental factors. Therefore, a more stable and objective molecular-based approach is needed, one of which is Single Nucleotide Polymorphism (SNP) analysis. This study aims to characterize the genetic diversity of mangoes in Cirebon using SNP markers as a basis for kinship information and potential variety development. The research methods included leaf sampling from several local Cirebon mango varieties, genomic DNA isolation, DNA amplification using the Polymerase Chain Reaction (PCR) method, and sequencing analysis to identify SNP variations. The SNP data obtained were analyzed to assess genetic diversity and kinship among mango varieties. The results showed genetic differences between local mango varieties that could be clearly distinguished using SNP markers. In conclusion, SNP-based characterization of Cirebon mango is effective for revealing genetic diversity and can serve as a basis for variety identification, preservation of local germplasm, and support for mango breeding and development programs in the Cirebon region.